In Vitro and In Vivo Evaluation of Mucoadhesive Microspheres for Treatment of Helicobacter pylori and Its Associated Diseases - Hardenia, Anu (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of the research work was formulation and systemically characterization of in vitro and in vivo activity of mucoadhesive microspheres of amoxicillin and famotidine for the effective use in the treatment of gastric and duodenal ulcers, which are associated with Helicobacter pylori. Such that the dual therapy gives better H. pylori eradication than single-drug therapy. The presence of two drugs in the same system will lead to improved efficacy of the system and increased patient compliance. Materials and Methods: Drugs containing mucoadhesive microspheres were prepared by an emulsion-solvent evaporation method using carbopol-934P as mucoadhesive polymer and ethyl cellulose as carrier polymer. The preliminary studies included the formulation of 27 batches of each drug using 33 factorial design. Optimization: A 33 factorial design was used to study the effect of independent variables, drug-to-polymer ratio (amoxicillin/famotidine-ethyl cellulose-carbopol-934P) (X1), concentration of emulsifying agent (X2), and stirring speed (X3) on dependent variables, drug entrapment efficiency (Y1), and particle size (Y2). Further, the in vitro mucoadhesion test was carried out for the mucoadhesion percentage and finally the in vivo studies (Bacterial clearance study, in vivo mucoadhesion and in vivo ulcer index studies) were carried out. Results and Discussion: Among the formulated batches, the batch A27 exhibited the best percent of mucoadhesion 66% after 10 h and F24 showed 74% of mucoadhesion after 10 h. Both batches were evaluated for in vivo performance. In the bacterial clearance studies, the mean bacterial count (log colony forming units) after oral administration of drug-loaded microspheres was found to be 3.72 Â± 0.58. The drug-loaded microspheres formulation exhibited better clearance from infection than plain drugs solution at the same doses. Drug microspheres formulation was found to be effective in the treatment of H. pylori infections effectively, and in in vivo mucoadhesion studies, the developed system was well taken up and processed by the cells of gastric mucosa of the stomach.